2002
DOI: 10.1074/jbc.c200504200
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin and NFAT4 Induce Chondrogenesis

Abstract: The vertebrate skeleton develops from a template that is initially constructed of cartilage. The formation of this template is controlled by a series of interdependent steps that supply spatial information and morphogenic cues that direct mesenchymal cell condensation and differentiation in a process known as chondrogenesis. Mesenchymal cells derived from the lateral plate mesoderm condense to form the rudiments of the appendicular skeleton. The processes that control the condensation of mesenchyme are poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 43 publications
5
72
2
1
Order By: Relevance
“…signals stimulate chondrocyte differentiation, and in other work (30), we show that the calcium-dependent pathway requires calcineurin. We showed that, when activated, calcineurin induces BMP2 gene expression and that differentiation in these culture systems proceeds via a BMP-dependent pathway (30).…”
Section: Fgf18 Represses Noggin 38211supporting
confidence: 76%
See 2 more Smart Citations
“…signals stimulate chondrocyte differentiation, and in other work (30), we show that the calcium-dependent pathway requires calcineurin. We showed that, when activated, calcineurin induces BMP2 gene expression and that differentiation in these culture systems proceeds via a BMP-dependent pathway (30).…”
Section: Fgf18 Represses Noggin 38211supporting
confidence: 76%
“…We showed that, when activated, calcineurin induces BMP2 gene expression and that differentiation in these culture systems proceeds via a BMP-dependent pathway (30). Calcium-dependent Signaling Induces FGF18 ExpressionTo further characterize the effects of calcium-dependent signals on chondrocyte differentiation and gene expression, we asked whether calcium signaling alters FGF18 gene expression.…”
Section: Fgf18 Represses Noggin 38211mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, NFAT4 activation upregulated BMP-2 expression, which in turn induced chondrogenesis. Since the above changes could be prevented by the CaN inhibitor CsA or the BMP antagonist noggin, the authors concluded that CaN/NFAT4 signalling activates BMP-2 expression and induces in vitro chondrogenesis [66]; thus they provided evidence that the phosphatase involved in the BMP-2 signalling pathway could indeed be CaN, according to the assertions of Tateishi and colleagues [65].…”
Section: Can Is An Important Regulator Of Chondrogenic Differentiationmentioning
confidence: 98%
“…Our group previously demonstrated that the changes of intracellular Ca 2+ concentration play an important role in cartilage differentiation [30]. Increased intracellular calcium levels can induce chondrogenesis through the Cn-nuclear factor of activated T-cells (NFAT) signaling pathway and modulate the activity of ERK1/2 [19,31]. The importance of the PPs in the regulation of chondrogenesis is doubtless but the effect of their overactivation and/or overexpression on cartilage differentiation has yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%